Developing Islamic City through Network-of-Mosque (NoM) - Nasution, Ammar Ihsan; Ahmad Dahlan, Abdul Rahman; Husaini, Muhammad Iqbal; Ahmed, Mohamed Hassan (International Foundation for Research and Development (IFRD), 2015)
Learning from the history, our prophet used mosque to provide many activities and served as community centre for the purpose of society welfare. Today, we can find the mosque everywhere but its function were limited and only used for religious and spiritual purposes. Thus, this conceptual program will develop the Islamic City through Network of Mosque. Network of Mosque can be used to create centre for transformation which can provide the services to the society. These services will include community classes, zakat collection and distribution, halal certification, and eating place for the hungry and needy. This conceptual program introduces to improve the quality of service through strategic partnership between government, industry, and society which will result to raise the entrepreneurs and lead to the prosperity. This program offers Quadruple Helix Model (QHM) which involves the Government, Academia, Industry, and Citizen as the main actor for this program. Nine blocks of Business Model Canvas (BMC) framework and Literature Review used as the methodology for this paper. To achieve its goals, this program collaborates and synergize with the Whole of Government (WoG). The findings of this paper show that the Mosque can facilitate and serve the society better by harnessing Network of Mosque, which guide to the developing Islamic City.